The Effect of Enterprise Resource Planning (ERP) Implementation on Operational Advances on The Quality of Financial Information at PT Pupuk Kujang in 2020 - Fulki Fathurrahman (International Journal Labs, 2021)
This study aims to determine how the effect of enterprise resource planning (ERP) implementation on quality financial information at PT Pupuk Kujang. This research is based on business changes due to increased competition which is marked by the needs of the company and related internal parties who are the perpetrators of ERP implementation in the development of the company's business activities, and also against the background of the implementation of an ERP system that produces inaccurate information. This research was conducted using quantitative methods with a survey approach. The data collected comes from questionnaires distributed to 63 respondents in related departments including accounting, finance, human resources (HR), marketing, sales facilities, retail sales, planning and promotion departments, industrial and general education and training. The results obtained indicate that ERP implementation can affect the quality of financial information through good implementation stages, supported by quality hardware and good human resources. However, there are also other factors that are not discussed in this study and have an influence on the quality of financial information.